A report of Second Workshop of IGCP-662 project “Orogenic architecture and crustal growth from accretion to collision” and Field excursion “Gobi Altai accretionary orogen”, July 4-10, Mongolia - Ochir, Gerel; Wang, Tao; Schulmann, Karel (Mongolian Geoscientist, 2019)
No Abstract in English